LEARNING STRATEGY FOR THE “KINANTHI” MACAPAT SONG IN SERAT WEDHATAMA AT RANDUDONGKAL STATE HIGH SCHOOL - Hikmah, Paojiatul; Gandung Joko Srimoko (Program Studi Pendidikan Musik, 2025)
Each level of education in Central Java has local content in the form of Javanese language subjects including SMANegeri 1 Randudongkal, divided into several materials in it, one of which is learning the tembang macapat kinanthi in wedhatama fiber. The learning of the macapat song, especially the kinanthi song, has several obstacles in theimplementation of learning both from educators and students. The purpose of this study was to determine the learning strategy of the